Diagnostic utility of trigeminocervical reflex and quantitative sensory testing in horses with trigeminal-mediated headshaking - Melanie J Käfer-Karrer; Claudia Spadavecchia; Mathieu de Preux; Lucia Unger (Journal of Veterinary Internal Medicine, 2026)
Abstract Background Assessment of trigeminal nerve (TN) function in horses with trigeminal-mediated headshaking (TMHS) using trigeminocervical reflex (TCR) and quantitative sensory testing (QST) has not been investigated. Hypothesis/Objectives Horses with TMHS show lower TCR and QST thresholds than controls. A subset shows left-to-right differences. Animals Privately owned horses with TMHS (n = 12) and secondary headshaking (sHS; n = 4), from a referral hospital. Headshaking-free controls (n = 14), from the hospital’s teaching herd or privately owned. Methods Prospective case–control-study. In unsedated horses, TCR was assessed using an automated threshold-tracking device via infraorbital nerve stimulation with concurrent splenic muscle electromyography. QST included evaluation of mechanical nociceptive, tactile sensory, and thermal nociceptive thresholds, assessed bilaterally at 2 sites. Group comparisons used t-tests or Mann–Whitney U tests. Univariate logistic regression assessed TCR and QST as predictors of TMHS. Results Horses with TMHS had significantly lower TCR thresholds than controls (0.82 ± 0.22 mA vs. 1.16 ± 0.30 mA, Hedges’ g = 1.24, 95% CI, 0.41-2.06, t = −3.31, P = .003), and logistic regression predicting TMHS showed good performance (R2 of 0.73, area under the curve of 0.83). No significant left-to-right differences were identified. In sHS horses, lower thresholds were observed on the affected side. QST revealed no significant differences between groups. Conclusions and clinical importance Lower TCR thresholds support altered TN function in TMHS. TCR might be a useful adjunct diagnostic tool, whereas QST did not identify affected horses, reflecting heterogeneous somatosensory phenotypes or limited sensitivity of the QST protocol.